ANALISIS STRATEGI PENGEMBANGAN POTENSI PARIWISATA BERKELANJUTAN (SUSTAINABLE TOURISM); STUDI KOMPARATIF DESTINASI PARIWISATA PANTAI JIMBARAN DAN PANTAI PASIR PADI - Rosalinda; R. Manullang, Rizal; Tri Setyo Mulyani, Hendarti (Jurnal Progresif Manajemen Bisnis, 2024)
Tourism is one of the potentials that must be developed by every region in Indonesia, of course with the concept of sustainable tourism by implementing the long-term sustainability of the tourism industry both on environmental, economic, and social impacts. The development of this potential cannot be separated from the strategies that must be launched and implemented in order to achieve the goals in the development of sustainable tourism. This research uses a comparative study between Jimbaran Beach and Pasir Padi Beach, to analyze the development strategy and potential of sustainable tourism on Jimbaran Beach as a source of reference in developing the development potential of Pasir Padi Beach in Pangkalpinang. Pasir Padi Beach is very potential to be developed and also requires support and participation from the community and government for its sustainability. The purpose of this research is to analyze and explain the development strategy of sustainable tourism potential by comparing Jimbaran Beach and Pasir Padi Beach tourist destinations because they have almost the same internal potential. This research is a qualitative research with a descriptive approach by emphasizing quantitative descriptive analysis. This research uses secondary data sources, namely data obtained indirectly such as literature studies, journals and websites. Based on the results and discussion of the research, it shows that the two destinations